Construction and Validation of the Perceived Opportunity to Craft Scale - van Wingerden, Jessica; Niks, Irene M. W. (Frontiers in Psychology, 2017)
We developed and validated a scale to measure employees’ perceived opportunity to craft in two separate studies conducted in the Netherlands (total N = 2329). Perceived opportunity to craft is defined as employees’ perception of their opportunity to craft their job. In Study 1 the perceived opportunity to craft scale (POCS) was developed and tested for its factor structure and reliability in an explorative way. Study 2 consisted of confirmatory analyses of the factor structure and reliability of the scale as well as examination of the discriminant and criterion-related validity of the POCS. The results indicated that the scale consists of one dimension and could be reliably measured with 5 items. Evidence was found for the discriminant validity of the POCS. The scale also showed criterion-related validity when correlated with job crafting (+), job resources (autonomy +; opportunities for professional development +), work engagement (+), and the inactive construct cynicism (−). We discuss the implications of these findings for theory and practice.